Multi-omics eco-surveillance of complex legacy contamination with a locally adapted estuarine invertebrate. (15th February 2023) - Hillyer, Katie E.; Bose, Utpal; Broadbent, James A.; Bissett, Andrew; Beale, David J.
Abstract: Complex legacy contamination from human use is a major issue for estuaries globally. In particular, contamination of water and sediments with bioavailable metals/metalloids, in addition to other industrial contaminants, such as hydrocarbons. Yet, understanding of complex toxicity and local adaptation in field exposed, non-model, invertebrate communities is limited. Herein, we apply multi-omics (metabolomics, lipidomics, proteomics) coupled to traditional sediment quality analyses, to better characterise molecular and cellular responses necessary for application to monitoring, as an eco-surveillance tool. Using these approaches, we characterise functional phenotypes of a sediment associated invertebrate (sipunculid), from an estuary exposed to complex legacy contamination (metals: Zn, Hg, Cd, Pb, Cu, As; and polycyclic aromatic hydrocarbons, PAHs). We sampled individuals at a range of exposure sites, highly (NTB5), moderately (NTB13), and lesser-influenced reference sites. Size differences were observed in sampled individuals between sites, with smaller individuals collected from NTB13. Analysis of environmental variables that correlated with change in the metabolite data revealed that the metabolism of smaller individuals at medium exposure NTB13 was highly differentiated by sediment concentrations of Hg, despite higher concentrations at more exposed NTB5. Functional phenotypes of these smaller individuals were characterised by sulphur and aromatic amino acid metabolism, increases in oxidised intermediates, upregulation of protein responses to oxidative stress, and melanin synthesis, and saturation of membrane and storage of lipids; in addition to the metabolism of naphthalene (PAH). Such widespread change was not observed in the metabolite and lipid profiles of larger individuals at high exposure NTB5, suggesting possible differences in effects between sites may also be associated with size (developmental stage, or age) and/or PAH exposure. This study serves to further understanding of differing modes of toxicity and local adaptation to multiple contaminants, and drivers of functional change in a complex estuary environment. Graphical abstract: Image 1 Highlights: Multi-omics applied as an ecosurveillance tool to complex estuary contamination. Metabolomics, lipidomics and proteomics analysis of a field exposed invertebrate. Change associated with exposure to heavy metals and naphthalene metabolites. Altered metabolism of sulphur and aromatic amino acids and nitric oxide pathways. Lipid and protein responses to oxidative stress and melanin synthesis upregulated.